Faktor Faktor yang Berhubungan dengan Perilaku Personal Hygiene saat Menstruasi pada Remaja Putri di SMA NEGERI 7 Kota Tangerang Selatan Tahun 2022 - Ratna Dyah Siti Asmara; Nur Asiah; Hidayati, Hidayati (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Reproductive organ infections can occur due to lack of attention to personal hygiene during menstruation. Appropriate information can help preventive efforts and many factors, such as knowledge, attitudes, support from family, peers, facilities and infrastructure, can influence personal hygiene behavior during menstruation in young women. This research aims to identify the factors that influence the personal hygiene practices of adolescent girls during menstruation in class X and This study used a cross-sectional design and took random samples from 338 study populations. The young women who were the subjects of this research were 197 respondents. Primary data was collected using a g-form questionnaire. This study used univariate analysis, as well as bivariate analysis using the chi-square test. Univariate results show personal hygiene behavior during menstruation in young women (68.5%), who have correct knowledge (38.1%), positive attitude (60.9%), supportive family support (53.8%), peers positive (66.7%), good facilities and infrastructure (63.5%). Bivariate results show there is a relationship between knowledge, family support and infrastructure (P value=<0.05), there is no relationship between attitudes and friends the same as personal hygiene behavior during menstruation. Based on this study, researchers provide suggestions for adolescents to maintain cleanliness and apply personal hygiene behavior during menstruation.